Iraq : Request for Stand-By Arrangement and Cancellation of Current Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report ;, 2008)
Iraq showed good progress in undertaking strong macroeconomic policies and implementing economic reforms under the Stand-By Arrangement (SBA). Executive Directors welcomed this, and noted that low investment and stagnating output in the oil sector continue to hamper economic growth. They stressed that the new SBA should maintain macroeconomic stability, facilitate higher investment and output in the oil sector, and move forward with key reforms that were initiated under the previous arrangement. They also emphasized for reduction in inflation, increase in international reserves, and implementation of structural reforms.